Industry 4.0 Transforming Global Retail Industry - Malar, Mercia Selva (Indian Journal of Computer Science, 2019)
Industry 4.0 is the term used for the current trend of automation and data exchange in manufacturing and the related supportive services technologies. Retail industry across the globe is embracing change in practices as presented and thrusted by Industry 4.0. Today we hear of Retail 4.0 as a result of Industry 4.0's influence on the practices of retail. Retail concepts have been influenced and transformed in terms of terminology and processes used for the basic components of retail, store spaces, logistics, and services extended by retailers. The paper is an attempt to examine how each aspect of Industry 4.0 has transformed the fundamental functioning of the retail industry. The study is an exploratory research based on published material on Industry 4.0 and retail industry.Â 